Mehanska detekcija signala magnetne resonance - Marinček, Sara Pia (Matrika, 2016)
We present a magnetic resonance imaging technique based on the measurement of magnetic force acting between a magnetic tip and the resonantly excited spins in the sample. In the first chapter we explain the physical background of magnetic resonance. In the second chapter we present the physical principles of mechanical detection and introduce its pros and cons in comparison to inductive detection. We also describe the image reconstruction procedure and present an interesting interdisciplinary experiment.
Keywords: detekcija signala; electron spin resonance; elektronska spinska resonanca; jedrska magnetna resonanca; magnetic resonance; magnetna resonanca; mechanical detection; nuclear magnetic resonance